Impact of Compensation and Work Environment on Employee Performance During the Covid 19 Pandemic: Investigations on Educational Institutions - Iskamto, Dedi; Ghazali, Puspa Liza; Afthanorhan, Asyraf; Rohim, Rabiatul Adawiyah Abdul; Arifin, Juliana; Zain, Eni Noreni Mohamad; Razak, Roslida Abdul (Communications in Mathematics and Applications, 2023)
The purpose of this study was to determine the effect of compensation and work environment on employee performance during the Covid-19 pandemic in Indonesia. The analysis in this study uses SPSS version 25. It was found that compensation has a positive and significant effect on employee performance, the work environment also has a positive and positive effect on employee performance. It was also found that compensation and work environment simultaneously affect employee performance. If we look at the R-square value of 0.847, it means that compensation and work environment can affect employee performance by 84.7%, while the remaining 15.3% is influenced by other variables not used in this study.
Keywords: Compensation; Work environment and employee performance